Impact of career social support on employability among university students in Shandong, China - JingJing, Huo; Mohd Noor, Mohd Asri (Journal of Islamic, Social, Economics and Development, 2026)
This study investigates the impact of career social support including encouragement from family, friends, and teachers, helps with career decision-making, reduces anxiety about the future and builds confidence through guidance. Employability including ability to secure and retain employment involves skills, attitude, and adaptability, influenced by education and experience and essential for career success. The study utilised a quantitative methodology, employing a structured survey administered to 100 university students in Shandong province. Descriptive statistics, correlation analysis, and multiple regression are used to identify how career social support affects employability outcomes. The correlation results showed that there is a moderate positive correlation (r = 0.487, p = 0.001) between career social support and employability among university students. This indicates that students who receive greater support from family, peers, and educators are likely to view themselves as more employable. Also, regression analysis shows that career social support accounts for 23.7% of the difference in employability (R² = 0.237), with an adjusted R² of 0.229 and a standard error of 0.278. This means that social support is a useful way to predict employability outcomes. The study emphasises the necessity of integrating career support systems into higher education to enhance graduates' employability. Family, friends, and teachers all help students feel more confident about getting and keeping a job. These findings underscore the necessity for universities to establish organised and supportive environments that foster student adaptability, self-confidence, and career preparedness. These findings enhance the literature on educational leadership and provide pragmatic guidance for policymakers and university administrators.